1994
DOI: 10.1159/000227365
|View full text |Cite
|
Sign up to set email alerts
|

Failure of Gonadotropin Releasing Hormone Therapy in Patients with Metastatic Ovarian Sex Cord Stromal Tumors

Abstract: Ovarian sex cord stromal tumors are usually indolent neoplasms that are generally confined to one or both ovaries at the time of diagnosis. The overall prognosis for these women is good though advanced or recurrent tumors occasionally occur. In such instances, if the tumor is localized, surgical or radiation therapy often provides good results; however, diffuse intra-abdominal disease is uncommon and difficult to treat effectively. Recently, synthetic gonadotropin releasing hormone (GnRH) analogue therapy has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…However, experience in treating GCT with hormonal agents is limited. Although several studies have reported the successful use of GnRH agonists (7, 8), negative results have also been reported (9). Furthermore, hormonal therapy has been attempted in cases of progressive GCTs that have failed to respond to chemotherapy and/or radiation.…”
Section: Discussionmentioning
confidence: 99%
“…However, experience in treating GCT with hormonal agents is limited. Although several studies have reported the successful use of GnRH agonists (7, 8), negative results have also been reported (9). Furthermore, hormonal therapy has been attempted in cases of progressive GCTs that have failed to respond to chemotherapy and/or radiation.…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al [75] have described PR with monthly GnRH agonists (leuprolide acetate 3.75 mg IM) lasting 3-11 months. A few other studies have shown response to GnRH agonists [73,74,77] while others showed no response to agonists and GnRH antagonists [78,79].…”
Section: Recurrent Gctmentioning
confidence: 99%
“…However, their possible use in the management of cancers in castrated or menopausal individuals, where they would turn into decreased gonadotrophin levels, has never been studied, as the rationale for this is currently missing. Similarly, clinical trials investigating gonadotrophin suppression for the treatment of rare, gonadotrophin-sensitive cancers, such as ovarian granulosa cell tumors, have been scanty and contradictory(Fishman, Kudelka, Tresukosol et al, 1996,Maxwell, Soisson andMiles, 1994). Thus, it is important to further characterize the biology of gonadotrophins and of their receptors in the setting of cancer.…”
mentioning
confidence: 99%